1987
DOI: 10.1007/bf00452866
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic results in cryptorchidism after combination therapy with LH-RH nasal spray and hCG

Abstract: Seventy-two boys with 81 cryptorchid testes were treated with combined LH-RH nasal spray and hCG in the period between 1983 and 1985. Cryptocur (LH-RH) was applied as nasal spray at a dose of 1.2 mg daily over a period of 14 days. In all of the patients, hCG treatment was carried out subsequently according to the WHO guidelines with five intramuscular injections at 2-day intervals. Primary treatment results considerably improved using the regimen. The rate of complete descent was 86.4% at the end of therapy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…While other studies have shown lower treatment success in the youngest patients [12,191, optimal effect was obtained in this study in 52% of 33 patients [l 11. In the other patient population, hCG was given immediately after treatment with GnRH, and testicular descent (to scrota1 bottom) was obtained for 86.4% of 81 initially undescended testicles in 72 boys [19]. Thus, the treatment success is lower in the present study than in the two uncontrolled studies mentioned above.…”
Section: Discussionmentioning
confidence: 47%
“…While other studies have shown lower treatment success in the youngest patients [12,191, optimal effect was obtained in this study in 52% of 33 patients [l 11. In the other patient population, hCG was given immediately after treatment with GnRH, and testicular descent (to scrota1 bottom) was obtained for 86.4% of 81 initially undescended testicles in 72 boys [19]. Thus, the treatment success is lower in the present study than in the two uncontrolled studies mentioned above.…”
Section: Discussionmentioning
confidence: 47%
“…Cryptorchidism has also been treated with synthetic analogs of LHreleasing hormone (LHRH) (42-44), and combined hormonal therapy with hCG and LHRH (45)(46)(47). The success rates have been reported to vary from 0 to 55% with hCG (48) and from 9 to 78% with LHRH (49).…”
Section: Discussionmentioning
confidence: 99%
“…Tag 1000 IV i. m. bei> 6jährigen (insgesamt 5000 IV)] nur unmittelbar nach ausbleibendem oder nur partiellem Erfolg der vierwöchigen Gn-RH-Therapie (Mißerfolg bei ca. 50%) empfohlen (34). Bei einer Nachbeobachtungszeit von 24 Monaten konnte mit dieser Therapie eine Senkung der Rezidivrate von 77 auf 30% erreicht werden (34 …”
Section: Medikamentöse Maßnahmenunclassified
“…50%) empfohlen (34). Bei einer Nachbeobachtungszeit von 24 Monaten konnte mit dieser Therapie eine Senkung der Rezidivrate von 77 auf 30% erreicht werden (34 …”
Section: Medikamentöse Maßnahmenunclassified